The Liberation of the Camps: The End of the Holocaust and Its AftermathDan Stone - McManus, John C. (2017)
The liberation of Nazi concentration camps elicits many powerful images in popular memory of World War II, perhaps the most poignant of which are the indelible scenes of joyful survivors mingling happily with the liberating soldiers who delivered them from almost certain extinction. The image of victims and saviors commingling in ecstatic fellowship seems to embody the very meaning of World War II in Europe, at least for Britons, Americans, and others in the West. It speaks to the destruction of a monstrous tyranny, the end of the Holocaust, and the triumph of representative, tolerant governments sensitive to the dignity of humanity over brutal, might-makes-right dictatorship.
Keywords: Rezension